Hypothyroid and Heart Disease - Rosita Wenilia (Yayasan Pendidikan Medika Indonesia, 2024)
Thyroid hormones, particularly T3 (triiodothyronine) and T4 (thyroxine), play a crucial role in regulating metabolism, growth, and cardiovascular function. Thyroid gland dysfunctions, such as hypothyroidism and hyperthyroidism, can have significant impacts on the cardiovascular system. Hypothyroidism is associated with reduced cardiac output, diastolic hypertension, and an increased risk of coronary heart disease (CHD), while hyperthyroidism can elevate heart rate and blood volume, potentially leading to cardiomyopathy. Epidemiological studies show that the prevalence of hypothyroidism is higher than hyperthyroidism, but it is often undiagnosed. Treatment of hypothyroidism involves the use of levothyroxine, aiming to normalize TSH and T4 levels through gradual titration. Special attention is required in treating patients with heart conditions to prevent complications such as myxedema coma. Therefore, early detection, prevention, and treatment of hypothyroidism are essential to reduce cardiovascular morbidity and mortality risks.